Comparison of Autofluorescence With Near‐Infrared Fluorescence Imaging Between Primary and Secondary Hyperparathyroidism. (11th December 2020) - Takeuchi, Mika; Takahashi, Takeshi; Shodo, Ryusuke; Ota, Hisayuki; Ueki, Yushi; Yamazaki, Keisuke; Horii, Arata
Abstract : Objectives: To examine the role of autofluorescence (AF) monitoring with near‐infrared fluorescence imaging (NIFI) in identifying parathyroid lesions in primary or secondary hyperparathyroidism (P‐HPT or S‐HPT) surgeries. Study Design: Prospective study. Methods: Twelve lesions each were resected from 12 and 3 patients with P‐HPT and S‐HPT, respectively. The mean and maximum AF intensities of the lesions normalized to that of the thyroid tissue for in situ and ex vivo preparations were compared between P‐HPT and S‐HPT. Subjective visual classifications of AF intensity were compared with postoperative quantitative assessments. The unevenness of AF distribution inside the lesions was assessed by determining the ratio of maximum to mean AF intensity and comparing them with the corresponding ratio for normal parathyroid glands (PGs). Results: In all quantitative comparisons (in situ/ex vivo, mean, and maximum AF), AF intensities of P‐HPT were stronger than those of S‐PHT. The AF‐positive rate in in situ subjective visual classification was higher for P‐HPT (100% vs. 33%). Subjective visual classifications showed a positive correlation with AF intensities. The ratio of maximum to mean AF was higher in P‐HPT and S‐HPT than in normal PGs. Conclusions: For P‐HPT, AF intensity in both in situ and ex vivo preparations was sufficiently high and correlated with the subjective visual classification, suggesting that NIFI may be useful for confirming P‐HPT lesions. In contrast, NIFI may have only a minor role in S‐HPT surgeries owing to the weak‐AF of S‐HPT lesions. HPT lesions show an uneven AF intensity distribution compared with normal PGs. Level of Evidence: 3 Laryngoscope, 131:E2097–E2104, 2021